Preparation and ring rolling processing of large size Ti-6Al-4V powder compact. (5th June 2016) - Guo, R.P.; Xu, L.; Zong, B.Y.; Yang, R.
Abstract: This study reports the feasibility to fabricate large size Ti-6Al-4V alloy parts using the retained powder after screened out the finer powder for additive manufacturing. Effects of powder size on the microstructure and mechanical properties of powder compacts were studied. Effects of HIPing cycle on relative density distribution of large size powder compact were also investigated. Hot compression tests of as-HIPed powder compact were conducted. Prediction of temperature field distribution of large size powder compact during ring rolling was obtained though finite element method (FEM). The results showed that the powder size has no obvious influence on the microstructure and mechanical properties of as -HIPed Ti-6Al-4V alloy. The homogeneous HIPed powder compact with large dimensions can be produced through an optimized HIPing schedule. The optimized hot working processing window from the isothermal compression tests is temperature at 940–970 °C and strain rate at 1–10 s − 1 . The hot workability of Ti-6Al-4V powder compact is comparable or better than that of as-cast alloys. On the basis of isothermal compression tests and FEM results, a large workpiece of Ti-6Al-4V powder component has been successfully formed by ring rolling, and the mechanical performance of ring-rolled powder compact have some improvements than that of as-HIPed alloys. Graphical abstract: Highlights: This work exploits a potential application for the retained Ti-6Al-4V powder after screening out the fine powder for AM. Large size Ti-6Al-4V powder compacts can be successfully produced through optimizing HIPing cycle. The hot workability of Ti-6Al-4V powder compact is comparable than that of as -cast alloys, or better. The mechanical properties of Ti-6Al-4V powder compact have some improvements after ring rolling.